The School Readiness in Implementing the Merdeka Curriculum in Pekanbaru : A Survey of Teachers and Students' Perspectives - Bastian, Adolf; Firdaus, M; Rizky, Ramanda (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to assess the school readiness in implementing the Merdeka Curriculum in the Year 2022/2023 at several SMA/SMK in Pekanbaru City. This study used a descriptive quantitative with a survey metod. Data collection techniques are carried out using questionnaires and observations, with a sample of 32 SMA/SMK selected through a purposive sampling technique. Data analysis techniques using descriptive analysis according to the variables that had been determined. Based on the research results show that the school's understanding of the Merdeka Curriculum was very high, reaching 94%. In total, 81% of SMA / SMK have met the requirements and have been appointed by the Indonesian Minister of Education, Culture, Research and Technology (Mendikbudristek) to implement the Merdeka Curriculum. Teachers' competence in supporting the Merdeka Curriculum reached 75%. In terms of students’ participation in effective learning, it is not optimal since it reached only 16%. It is necessary to improve policy and procedural support, around 62% stated this. However, only 56% of schools use learning modules from the Mendikbudristek. Besides, the use of the Minimum Competency Assessment (MCA) and Character Survey also reached 56%, while the use and preparation of independence learning lesson plans reached 62%. In conclusion, a number of challenges remain in the implementation of the Merdeka Curriculum in SMA/SMK, especially related to infrastructure, student participation, and policy support, but it has also achieved some level of success in terms of teacher competence and the use of teaching materials.